1998
DOI: 10.1016/s0001-2092(06)62646-x
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Nursing Care When Sudden Patient Death Occurs in the OR

Abstract: This article explores how nurses cope with sudden death in the OR. It reviews the literature on this topic and explores grief and bereavement models, as well as provides a discussion of clinical coping methods identified through nursing experience. An education model presents information about implementing nursing care for the patient and family members. Critical care nursing research has been used to develop the model with adaptation to the perioperative setting. The model discusses the value of support for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
4
0
3
Order By: Relevance
“…Consistent with Brunelli (2005) and Mulligan (2004), findings from this study also recognize that nurses experience conflicting states of mind in that they must remain strong for the patient or family, while at the same time compartmentalizing the pain they may feel for the loss of the relationship with the patient or family. In fact, Onstott (1998) found that OR nurses compartmentalized, in a way, by "remaining calm" so that they could stay focused on the task and grieve later.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with Brunelli (2005) and Mulligan (2004), findings from this study also recognize that nurses experience conflicting states of mind in that they must remain strong for the patient or family, while at the same time compartmentalizing the pain they may feel for the loss of the relationship with the patient or family. In fact, Onstott (1998) found that OR nurses compartmentalized, in a way, by "remaining calm" so that they could stay focused on the task and grieve later.…”
Section: Discussionmentioning
confidence: 99%
“…C'est ainsi que les auteurs proposent -pendant la réanimation -d'informer la famille sur son déroulement, clairement et avec empathie, au mieux toutes les 15 minutes et, dans les faits, le plus souvent qu'il sera possible. Ainsi, la famille se sent impliquée, elle se rend compte que « tout ce qui est possible est réalisé » et l'équipe soignante a la possibilité de créer un climat de confiance avec la famille et de la préparer au pire [2,3]. Certains proposent même de faire entrer la famille en salle de réanimation quand cela est possible.…”
Section: Comment Annoncer Le Décès à La Famille ?unclassified
“…Elle devrait notamment pouvoir l'accompagner pour aller voir le corps si elle le désire (sinon il faut toujours respecter la décision de la famille, surtout si elle ne veut pas voir le corps) [2]. Si elle le souhaite, on peut laisser la famille participer aux soins de la défunte [3] en portant attention aux rites particuliers à respecter en fonction des religions, croyances ou autres [6,8] documents nécessaires pour les funérailles [6,9], associations qui s'occupent du deuil (livrets explicatifs concernant les démarches, le processus de deuil. .…”
Section: Comment Annoncer Le Décès à La Famille ?unclassified
See 1 more Smart Citation
“…Medical students at these pioneering medical schools were obligated to pay for and attend the funerals of their cadavers. Today, the tradition of cadaver dissection in the United States relies on the generosity of donors [4] and remains at the core of medical education. The study of human anatomy through cadaver dissection is often regarded as a rite of passage to the practice of medicine.…”
Section: Introductionmentioning
confidence: 99%